2012
DOI: 10.1007/s00299-012-1375-0
|View full text |Cite
|
Sign up to set email alerts
|

Structure and expression profiling of a novel calcium-dependent protein kinase gene, CDPK3a, in leaves, stems, grapes, and cell cultures of wild-growing grapevine Vitis amurensis Rupr.

Abstract: KEY MESSAGE : VaCDPK3a is actively expressed in leaves, stems, inflorescences, and berries of Vitis amurensis and may act as a positive growth regulator, but is not involved in the regulation of resveratrol biosynthesis. Calcium-dependent protein kinases (CDPKs) are known to play important roles in plant development and defense against biotic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 48 publications
(28 citation statements)
references
References 41 publications
0
28
0
Order By: Relevance
“…It was obtained by Agrobacte rium mediated transformation with a binary vector carrying the kanamycin resistance gene. The resulting cell line KA O had the same phenotype as the original cell culture V2 [18].…”
Section: Plant Materials and Cell Culturementioning
confidence: 87%
See 2 more Smart Citations
“…It was obtained by Agrobacte rium mediated transformation with a binary vector carrying the kanamycin resistance gene. The resulting cell line KA O had the same phenotype as the original cell culture V2 [18].…”
Section: Plant Materials and Cell Culturementioning
confidence: 87%
“…The selection of trans genic cells was performed by selection on kanamycin (10-15 mg/L) for three months. The produced trans genic lines were determined with primers 5'GAGGC TATTCGGCTATGACTG and 5'ATCGGGAGCG GCGATACCGTA by the presence of nptII gene inser tion under the conditions described in [18]. PCR for the virB2 gene was performed with primers 5'AAT GCGCGTGATATCGAGCTGCG and 5'ATACTAC CGCCAGTGAGCGTTTGG.…”
Section: Plant Materials and Cell Culturementioning
confidence: 99%
See 1 more Smart Citation
“…Total RNA isolation was performed using hexadecyltrimethylammoniumbromide‐based extraction as descried in . Complementary DNAs were synthesized as described previously .…”
Section: Methodsmentioning
confidence: 99%
“…Application of a calmodulin antagonist, N-(6-Aminohexyl)-5-chloro-1-naphthalenesulfonamide (W7), which is known as an inhibitor of CDPK activities, considerably reduced accumulation of resveratrol and expression of STS genes in grapevine cell cultures with the salicylic acid (SA)-and precursor-induced stilbene accumulation (Kiselev et al 2013a). In our recent investigations, we found that overexpression of CPK20 and CPK29 genes in grapevine cell cultures considerably increased tresveratrol production, while overexpression of CPK3a, CPK9, CPK13, and CPK21 genes did not have a consistent positive effect on stilbene production (Kiselev et al 2013b;Aleynova-Shumakova et al 2014;Aleynova et al 2015;Dubrovina et al 2016). These results indicate that some CDPKs are implicated in the regulation of stilbene biosynthesis as positive regulators.…”
Section: Signaling Pathways Regulating Stilbene Biosynthesis Regulatimentioning
confidence: 99%